2009
DOI: 10.1080/00071660903365612
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic responses of broilers. III. Tibial breaking strength and ash content

Abstract: 1. A total of 7960 Cobb and Ross broiler males were reared on various photoperiods or continuous illumination in two trials to 35 or 40 d. Tibial breaking strength was measured in both, and tibial ash content determined in the first of the two trials. 2. Tibial breaking strength was significantly affected by photoperiod, body weight, testicular weight, and genotype. Although peak bone strength occurred at about 7 h for Ross and at 12 h for Cobb, with reductions in strength for both shorter and longer photoperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
6
26
0
Order By: Relevance
“…Further, Onba ılar et al (2007) reported that chickens reared in IL had numerically lower tibial dyschondroplasia values. As well, prior reports indicated that tibial breaking strength was significantly affected by photoperiod and genotype, and that peak bone strength was achieved with a 7 h lighting period, with reductions in strength apparent following both shorter and longer photoperiods (Lewis et al, 2009). In the present experiment, no leg abnormalities were detected among the three experimental treatments; however, the bone elastic modulus of birds reared in the 4L:4D photoperiod was greater than the corresponding measurements obtained from birds in the other two photoperiod treatments, which indicated that the 4L:4D photoperiodic lighting perhaps favored tibial growth in broilers.…”
Section: Tibia Parametersmentioning
confidence: 83%
“…Further, Onba ılar et al (2007) reported that chickens reared in IL had numerically lower tibial dyschondroplasia values. As well, prior reports indicated that tibial breaking strength was significantly affected by photoperiod and genotype, and that peak bone strength was achieved with a 7 h lighting period, with reductions in strength apparent following both shorter and longer photoperiods (Lewis et al, 2009). In the present experiment, no leg abnormalities were detected among the three experimental treatments; however, the bone elastic modulus of birds reared in the 4L:4D photoperiod was greater than the corresponding measurements obtained from birds in the other two photoperiod treatments, which indicated that the 4L:4D photoperiodic lighting perhaps favored tibial growth in broilers.…”
Section: Tibia Parametersmentioning
confidence: 83%
“…Feed intake was higher for 24L compared to applying a lighting schedule and higher for the 2L:1D lighting schedule than for the 2L:6D lighting schedule in both experiments. Lewis et al (2009) demonstrated that broilers will learn to eat in dark when they are kept under prolonged (> 16 h) dark periods in a lightproof room, similar to the present study. However, they subjected broilers to an uninterrupted dark period (Lewis et al, 2009), whereas the dark period in the present study lasts a maximum 6 h at a time.…”
Section: Discussionsupporting
confidence: 88%
“…Lewis et al (2009) demonstrated that broilers will learn to eat in dark when they are kept under prolonged (> 16 h) dark periods in a lightproof room, similar to the present study. However, they subjected broilers to an uninterrupted dark period (Lewis et al, 2009), whereas the dark period in the present study lasts a maximum 6 h at a time. This may have decreased the broiler's incentive to start eating in the dark compared to a continuous long dark period, and resulted in lower overall feed intake for the 2L:6D lighting schedule compared to the other treatments.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…From June 2010, new EU animal welfare regulations included stopping the use of lighting regimen with day length longer than 18 h to improve broiler welfare. Therefore, several different types of photoperiods have been tested to decrease susceptibility to metabolic diseases, skeletal disorders, and increase tibial breaking strength (Renden et al 1996;Ingram et al 2000;Sanotra et al 2002;Lewis et al 2009;Schwean-Lardner et al 2012. Moreover, lighting regimens maintain the vitality of anatomical stress indicators such as liver (Onbasilar et al 2007;Bayram and Ozkan 2010) and bursa of fabricius and spleen, which are main organs that could refer to the immunological status as well (Pope 1991;Heckert et al 2002;Blahova et al 2007;Ahmed and El-Ghamdi 2008).…”
Section: Introductionmentioning
confidence: 99%